Willingness to Pay Model for Motorcyclists’ Slight Injuries in Jember - Willy Kriswardhana; Nunung Nuring Hayati; Karina Dea Puspita (Institut Teknologi Bandung, 2020)
The growth of transportation facilities and infrastructure is not in line with traffic growth, resulting in an increase in traffic crashes. The increasing trend in the number of crashes causing death occurs in developing countries, like Indonesia. The purpose of this study is to value the subjective cost of a slight crash. This study used the Willingness to Pay method to determine the probability of motorists to be willing to pay more to reduce the risk of traffic crashes using the binary logistic regression method. The results of the Willingness to Pay method provide conclusions namely gender, total income, marital status, and the experience of having an crash resulting in the probability of being willing to pay more to reduce the risk of crashes by 27% (for motorists who have had an crash one time) and 40% (for motorists who have had a crash twice).